2011
DOI: 10.3855/jidc.1758
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative ocular infection due to Streptococcus dysgalactiae subspecies equisimilis

Abstract: Ocular infections due to Streptococcus dysgalactiae subsp. equisimilis are rare. In the present report, three patients with a history of uncomplicated small incision cataract surgery with intraocular lens implantation developed exogenous endophthalmitis due to Streptococcus dysgalactiae subsp. equisimilis. The identification of the organisms was confirmed by PCR for a 16S rRNA sequence specific to the species S. dysgalactiae. Intravitreal treatment of cefazolin and amikacin, in addition to topical ofloxacin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…However, epidemiology of exogenous endophthalmitis with S. dysgalactiae could be probably underestimated in ophthalmologic infectious aspect. Kaliamurthy et al [14] reported three patients with a history of uncomplicated cataract surgery developed exogenous endophthalmitis due to S. dysgalactiae. Intravitreal (cefazolin, amikacin) and topical (ofloxacin, tobramycin) antibiotic treatments resulted in resolution of infection in all three patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, epidemiology of exogenous endophthalmitis with S. dysgalactiae could be probably underestimated in ophthalmologic infectious aspect. Kaliamurthy et al [14] reported three patients with a history of uncomplicated cataract surgery developed exogenous endophthalmitis due to S. dysgalactiae. Intravitreal (cefazolin, amikacin) and topical (ofloxacin, tobramycin) antibiotic treatments resulted in resolution of infection in all three patients.…”
Section: Discussionmentioning
confidence: 99%
“…This case report becomes rare, as this is the first case where the etiology for basal gangliar abscess is Group G streptococcus. There are few case reports in which Streptococcus milleri, pseudomonas [4], Peptostreptococcus, streptococcus Group F have been isolated from basal gangliar and thalamic abscess [5]. The most common site of brain abscess is the temporal lobe abscess with CSOM as the predisposing factor [6].…”
Section: Discussionmentioning
confidence: 99%
“…pasteurianus n = 4 [ 105 ] <2 weeks Streptococcus salivarius n = 65 Iatrogenic 67 %; cerebrospinal fluid leak (head injury, neurosurgical treatments) 21 % Beta-lactams (penicillin or cephalosporin), vancomycin 2 [ 58 ] Streptococcus intermedius 70/F Lack Carbapenems, vancomycin, ceftriaxone, ampicillin N [ 106 ] Streptococcus pneumoniae n = 3 Meningitis; long-term neurological deficit [ 107 ] Adults Cases of eye infection Streptococcus mitis 85/M Complicated endocarditis Vancomycin, amikacin, levofloxacin, ampicillin, ceftriaxone, gentamicin N [ 108 ] Streptococcus uberis 52/M Postoperative endophthalmitis Ceftazidime, vancomycin, dexamethasone, ampicillin, moxifloxacin N [ 109 ] Streptococcus bovis 47/M Alcoholism Vancomycin, ceftazidime, dexamethasone N [ 110 ] Streptococcus dysgalactiae subsp. equisimilis 50/F Eye surgery Cefazolin, amikacin, ofloxacina, tobramycin N [ 111 ] 75/M 62/M Iatrogenic infection Streptococcus pneumoniae n = 32 Lack of vaccination against S. pneumoniae /Young age of the patient [ 112 ] <2 years of age Streptococcus mitis / ...…”
Section: Sepsismentioning
confidence: 99%